Implikasi Yuridis Putusan Mahkamah Konstitusi Nomor 62/PUU-XXII/2024 terhadap Mekanisme Pencalonan Presiden dan Wakil Presiden di Indonesia - Ashari, Muhammad; Ardiansah, Ardiansah; Andrizal, Andrizal (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
The implementation of the presidential threshold in Indonesia has long been debated for its impact on political representation and democratic fairness. As a response to ongoing criticism, the Constitutional Court issued Decision No. 62/PUU-XXII/2024, which annulled Article 222 of Law No. 7 of 2017 concerning the requirement for political parties or coalitions to meet a minimum seat or vote percentage to nominate presidential and vice-presidential candidates. This study explores the legal consequences of that ruling on Indonesia’s presidential nomination system. Using a normative juridical method with qualitative analysis, the research is based on constitutional interpretation, relevant statutory provisions, and scholarly perspectives on constitutional law and judicial review. The ruling emphasizes the incompatibility of the threshold with the principle of popular sovereignty and reaffirms the Constitutional Court’s function as the guardian of constitutional rights. The elimination of the threshold opens broader access for political parties to participate in presidential nominations, increases leadership choices for voters, and challenges the dominance of major parties. Nevertheless, the decision also demands prompt legislative reforms and institutional readiness to ensure a smooth transition toward a more inclusive and democratic electoral process.